Synthesis and Characterization of Poly(methyl methacrylate) Brushes on Silica Particles by Surface-Initiated Atom Transfer Radical Polymerization - Liu, Hui; Cui, Huanqing; Wang, Ruimeng; Chen, Si; Zhou, Wanzhu (Asian Journal of Chemistry, 2014)
We synthesized herein poly(methyl methacrylate) (PMMA) brushes from silica particles via surface-initiated atom transfer radical polymerization. The resulting polymer brushes were characterized by means of Fourier transform infrared spectra, thermal gravimetric analysis, X-ray photoelectron spectrometer and transmission electron microscope. The molecular weight and distribution of free polymer were analyzed by gel permeation chromatography and it was found that molecular weight (Mn) decreased from 40600 to 14200 with the increasing free initiator concentration and polydispersities index ranged from 1.26 to 1.49.